Environmental DNA Monitoring of Biodiversity Hotspots in Danish Marine Waters - Staehr, Peter A. U.; Dahl, Karsten; Buur, Helle; Göke, Cordula; Sapkota, Rumakanta; Winding, Anne; Panova, Marina; Obst, Matthias; Sundberg, Per (Frontiers in Marine Science, 2022)
We investigated the use of eDNA metabarcoding for supplementing traditional diver-based monitoring of biodiversity of marine boulder reefs within the photic zone. The applied sampling design, made it possible to evaluate the usefulness of eDNA monitoring as a supplement for traditional monitoring. Specifically, this study aimed to1) assess the local influence of boulder reefs on biodiversity across the North Sea to Baltic Sea transition zone and 2) investigate the importance of environmental gradients for patterns in community structure. On samples collected during August 2020, we compared the composition and abundance of species associated with nine reefs, representing an environmental gradient of salinity (16 to 33 psu), water temperature (16 to 21⁰C) and water depth (6 to 29 m). At each reef site, water was sampled near the bottom, of the reef and on average 2.6 km upstream and downstream (location) and sequenced with metabarcoding using COI, 18S and 12S rDNA primers. eDNA identified 400 species, diver based observations identified 184 with an overlap of 70 species (12%) and 81 genera (18%). While eDNA identified many infaunal species, it did not detect several macroalgal species which dominated in the diver based observations. Multivariate analysis of eDNA and diver derived community structure both distinguished between reef communities, with a significant match between patterns observed by the two methods (r = 0.37, p = 0.02). Furthermore, the eDNA approach made it possible to identify significant differences in species composition between upstream, reef and downstream sites, suggesting that eDNA leaves a local footprint in benthic habitats. Patterns in both eDNA and diver based species composition and richness were significantly related to geographical distance, salinity, water temperature and water depth. Despite of low detection of macroalgae, the eDNA sampling provided a substantial supplement to traditional diver based monitoring of biodiversity around benthic hotspots in the Danish marine waters and therefore we recommend to add eDNA methods to conventional monitoring programs in the future.